The RRM protein NonA from Drosophila forms a complex with the RRM proteins Hrb87F and S5 and the Zn finger protein PEP on hnRNA. - Reim, Ingolf; Mattow, Jens; Saumweber, Harald (Experimental Cell Research, 1999)
The RRM protein NonA, an ubiquitous nuclear protein present in puffs on polytene chromosomes, has been immunopurified as a RNA-protein complex from Drosophila Kc cells. Three other proteins present in the complex have been identified: X4/PEP (protein on ecdysone puffs), a 100-kDa zinc finger RNA-binding protein; the 70-kDa S5 protein, an as yet uncharacterized RNA-binding protein; and P11/Hrb87F, a 38-kDa RRM protein homologous to hnRNP protein A1 from mammals. Monoclonal antibodies against any of the protein components coprecipitate all four proteins although at different ratios. NonA does not coprecipitate with the hrp40 hnRNP proteins and immunolocalizes in a pattern distinct of major hnRNP proteins. Like NonA, X4/PEP, S5, and P11/Hrb87F are present on active sites on polytene chromosomes. The precipitated NonA complex is enriched for certain protein encoding RNAs, notably, histone H3 and H4 RNA.